The soft drinks companion : a technical handbook for the beverage industry / (Acc. 6406) - Shachman, Maurice (New York : CRC Press, 2019)
This comprehensive book presents key issues in the technology of the soft drinks industry. Employing a user-friendly format and writing style, the author draws on more than thirty-five years' Hands-on experience in technical management in the soft drinks industry. The diverse subjects discussed focus on key scientific and technical issues encountered by technical Staff at all levels on a daily basis, including cost factors related to technical subjects. The succinct explanations of scientific concepts underlying technology issues and potential problems make the soft drinks companion an ideal all-around reference for both the professional and novice.
Keywords: 1.Soft drinks. 2. Beverage industry 3. Technical handbook